Facet-dependent performance of BiOBr for photocatalytic reduction of Cr(vi). Issue 3 (4th January 2016) - Fan, Zao; Zhao, Yubao; Zhai, Wei; Qiu, Liang; Li, Hui; Hoffmann, Michael R.
Abstract : BiOBr dominated with 110 facets giving a specific rate constant 3 times as high as BiOBr with 001 facets, and its much stronger internal electric field was believed to be the main reason. Abstract : BiOBr samples with different facets were prepared and used for photocatalytic reduction of hexavalent chromium under visible light. The results reveal that BiOBr dominated with 110 facets giving a specific rate constant 3 times as high as BiOBr with 001 facets, and its much stronger internal electric field was believed to be the main reason.